Agroeconomical and agroecological aspects of the rye (Secale cereale L.) yelds spatial variation within Polesia and Foreststeppe zones of Ukraine: the useage of the geographically weighted principal components analysis - Kunah, O.M.; Кунах O. M.; Pakhomov, O.Ye.; Пахомов, O. Є.; Zymaroieva, А. А.; Зимароєва, А. А.; Demchuk, N. I.; Демчук, Н.І.; Skupskyi, R.M.; Скупский, Р.M.; Bezuhla, L.S.; Безугла, Л.С.; et al. (My University, 2018)
In the present article the patterns of the geographic variability in yields of rye within Polesia and Foretsteppe zones of Ukraine were established and the correlation of the factors and dynamics of the agroeconomic and agroecological nature was determined. The dynamics yields of rye in the study area over time were determine as being characterized by three extreme points: two local maxima and one local minimum. Specific terms of polynomial curve of the fourth order can be meaningfully interpreted and applied to describe the dynamics of productivity. Free member of the polynomial indicates culture productivity in the starting period. Dynamics of the productivity that can be explained by the regression indicates that agrotechnological and agrecological conditions of agricultural production is a pervasive factor that determines the presence of a general trend. Determination coefficient of the regression total trend can be interpreted as an indicator of the role of the agrotechnological and agroeconomical factors in the dynamics of productivity. Residue of the trend regression model can be interpreted so as to include agriecological component of the rye yields dynamics. Their analysis revealed seven key components that together explained 58.4% of the total variability of the feature space. The principal components of vibrational patterns reflect the specific nature of variation over time yields of rye, which are spatially defined. Vibrational effects are environmental in nature. Geographically weighted principal component analysis showed the transience of environmental spatial modes which determine the oscillating component of rye yield variation over time. Spaces within which the structure of ecological interactions remains unchanged, can be considered as the basis of agroecological zoning areas. В даній статті були встановлені закономірності географічної мінливості врожаю жита в межах Полісся і передгірських зон України та визначено співвідношення факторів і динаміки агроекономічної та агроекологічної природи. Динаміку врожайності жита в досліджуваній області з часом визначали як характеризуються трьома крайніми точками: двома локальними максимумами та одним локальним мінімумом. Специфічні терміни поліноміальної кривої четвертого порядку можуть бути осмислені і застосовані для опису динаміки продуктивності. Вільний член полінома вказує на продуктивність культури в початковому періоді. Динаміка продуктивності, що можна пояснити регресією, вказує на те, що агротехнологічні та агрегологічні умови сільськогосподар-ського виробництва є поширеним фактором, що визначає наявність загальної тенденції. Коефіцієнт детермінації загальної тенденції регресії можна інтерпретувати як показник ролі агротехнологічних та агроекономічних факторів у динаміці продуктивності. Залишок моделі регресійної тенденції можна інтерпретувати так, щоб включити агроекологічну складову динаміки урожаю жита. Їх аналіз виявив сім ключових компонентів, які разом пояснювали 58,4% загальної мінливості простору ознак. Основні компоненти коливальних моделей відображають специфіку зміни часових врожаїв жита, які є просторово визначеними. Вібраційні ефекти носять екологічний характер. Аналіз географічно зважених основних компонентів показав швидкоплинність просторових режимів навколишнього середовища, які визначають коливальний компонент варіації врожаю жита у часі. Простір, в межах якого структура екологічних взаємодій залишається незмінною, може розглядатися як основа агроекологічних районування районів.
Агроекономічні та агроекологічні аспекти просторової зміни жита в межах Полісся і Лісостепу України: використання географічно зважених основних компонентів
Keywords: geographically weighted principal component analysis; аналіз географічно зважених основних компонентів; yield; врожай; corn; жито; spatial variability; просторова мінливість; temporal dynamics; тимчасова динаміка